2021
DOI: 10.3389/fgene.2021.620705
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tumor Microenvironment-Related Prognostic Genes in Sarcoma

Abstract: AimImmune cells that infiltrate the tumor microenvironment (TME) are associated with cancer prognosis. The aim of the current study was to identify TME related gene signatures related to the prognosis of sarcoma (SARC) by using the data from The Cancer Genome Atlas (TCGA).MethodsImmune and stromal scores were calculated by estimation of stromal and immune cells in malignant tumor tissues using expression data algorithms. The least absolute shrinkage and selection operator (lasso) based cox model was then used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
(56 reference statements)
4
6
0
Order By: Relevance
“…62 In STS too, recent clinicogenomic models have been published as nomograms through analysis of immune genes in the TCGA series, but without effort of validation in an independent set. [28][29][30] Our model is the first one to show robustness in a validation set (339 samples), in which we confirmed better prediction accuracy than that achieved by using either clinical data or genomic signature alone.…”
Section: Biological and Therapeutic Correlates Of The Two Prognostic Groupssupporting
confidence: 68%
See 2 more Smart Citations
“…62 In STS too, recent clinicogenomic models have been published as nomograms through analysis of immune genes in the TCGA series, but without effort of validation in an independent set. [28][29][30] Our model is the first one to show robustness in a validation set (339 samples), in which we confirmed better prediction accuracy than that achieved by using either clinical data or genomic signature alone.…”
Section: Biological and Therapeutic Correlates Of The Two Prognostic Groupssupporting
confidence: 68%
“…In a reanalysis of the TCGA dataset, an association between shorter overall survival and lower immune scores, CD4+ T cells and CD8+ T cells estimated using ESTIMATE and TIMER deconvolution algorithms was reported. 30 In a study dedicated to UPS, two groups ('immune-high' and 'immune-low') were identified from gene expression profiles and confirmed at the proteomic level. 27 When compared with the 'immune-low' group, the 'immune-high' group showed longer overall survival, higher tumor mutational burden, and lower copy number alterations rate, and lower sensitivity to FGFR inhibition.…”
Section: Biological and Therapeutic Correlates Of The Two Prognostic Groupsmentioning
confidence: 97%
See 1 more Smart Citation
“…Because CSPG4 is the target of cellular immunotherapy, we searched for correlations of its expression in tumors with several immune variables. In each data set separately, several immunity-related multigene classifiers were applied to each tumor: the 24 Bindea’s innate and adaptative immune cell subpopulations [ 27 ], the Immunologic Constant of Rejection (ICR) classifier [ 28 ], and metagenes associated representative of T-cell-inflamed signature (TIS) [ 29 ], of tertiary lymphoid structures (TLS) signature [ 30 ], of cytolytic activity score [ 31 ], of IFNα and IFNγ pathways activation score [ 32 ], the antigen processing machinery (APM) score [ 33 ], and ESTIMATE scores (Immune infiltration, Stromal infiltration, Tumor purity) [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…At present, the molecular regulatory mechanisms of sarcoma have not yet been fully elucidated. Notably, an increasing number of studies have shown that changes in the tumor immune microenvironment (TIME) play a key role in the occurrence and development of sarcoma [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%